GAMBARAN BERBAGAI ASPEK KESEHATAN LINGKUNGAN DENGAN INSPEKSI KESEHATAN LINGKUNGAN (IKL) PADA SEKOLAH DASAR DI WILAYAH KERJA PUSKESMAS KERAMASAN KOTA PALEMBANG TAHUN 2023 - Seflin; Sari Murni, Nani; Wahyudi, Arie; Yusnilasari (Avicenna: Jurnal Ilmiah, 2023)
Background: Decree of the Minister of Health Number 1429 of 2006 concerning Guidelines for Implementing School Environmental Health, states that environmental health requirements cover several aspects including aspects of school canteen buildings and school sanitation facilities. Four Elementary Schools that have undergone Environmental Health Inspections, and 3 Elementary Schools that meet health requirements from 16 Elementary Schools in the working area of the Keramasan Health Center in 2021. This research aims to find out various aspects of Environmental Health with Environmental Health Inspections (IKL) in Elementary Schools (SD) in the Working Area of the Keramasan Health Center in Palembang City in 2023. Method: This study uses a cross sectional design. The population in this study is 16 SD. The research sample was taken by total sampling technique, namely 16 elementary schools. Data collection was carried out for 6 days from 12 -17 June 2023. Data was collected using a questionnaire, then univariate analysis was carried out. Results: The results showed that the distribution of the frequency of Environmental Health Inspections in 16 Elementary Schools that met the requirements was 12.5%. Water health for the most part TMS (81.3%), Air quality for TMS and MS schools respectively 50%, Facilities and buildings for most TMS school facilities and buildings (81.3%), TMS school canteens (62.5%), Vectors and TMS disease-carrying animals (81 ,3%). Conclusion: The conclusion from the results of this study is that water health, air quality has an Environmental Health Inspection that meets the requirements, while the Health of Water, Facilities and Buildings, School Canteens, Vectors and disease-carrying animals has an Environmental Health Inspection that doesn’t meet the requirements. It is suggested that the Environmental Health Inspection in schools should provide good sanitation facilities for the school environment. Keywords : Environmental Health, Environmental Health Inspection, Elementary School